Interrelationship of hydrology, microbial colonisation and hydrometallurgy in a simulated chalcopyrite heap leach - Spurr, Nicholas Robert Louis (Centre for Bioprocess Engineering Research, 2015)
Includes bibliographical references (leaves 104-115).